Ethanolic Extract of Stachys byzantina Leaf: Optimization of Ultrasonic Probe-Assisted Extraction and Characterization - Dias, Sthefany Lorena Gemaque; Raspe, Djéssica Tatiane; Júnior, Oscar de Oliveira Santos; Agneis, Maria Luisa Gonçalves [UNESP]; Seiva, Fabio Rodrigues Ferreira [UNESP]; Garcia, Vitor Augusto dos Santos [UNESP]; Cardozo-Filho, Lúcio; Silva, Camila da (MDPI, 2025)
The present study aimed to apply ultrasonic probe-assisted extraction (UPAE) using ethanol as a solvent to separate compounds from Stachys byzantina leaves. Experimental tests were carried out to investigate the influence of temperature (T) (30, 45 and 60 °C), ultrasonic amplitude (UA) (30, 60 and 90%) and extraction time (ET) (10, 15 and 20 min) on the extraction yield (EY). The extracts obtained at different extraction times were characterized for compound profile, soluble protein content, and antioxidant potential. The cytotoxic effect of the extract was also evaluated. The greatest mass recovery (19.8 wt%) was verified at the highest levels of the variables. The total phenolic compound content and antioxidant potential increased with the application of extraction times of 5 to 20 min, at 60 °C and UA of 90%. The extracts contained ~25 wt% of soluble protein. The extracts showed a predominance of chlorogenic, protocatechuic, and syringic acids. Nicotinic acid was also detected in the extracts, with levels ranging from 11.91 to 13.86 mg/100 g. The fatty acid profile indicated the presence of lauric, palmitic and linolenic acids in higher concentrations, with quantification of squalene, α-tocopherol and β-sitosterol. The ethanolic extract of Stachys byzantina showed no cytotoxic effect on HaCaT cells at concentrations up to 200 µg/mL, maintaining cell viability above 70% after 48 h of exposure.